Ethnopharmacology, LC-MS profiling, and molecular docking of diarrheal-healing plants by the Osing tribe - Cendekiawan, Khrisna Agung; Kintoko; Yuliani, Sapto; Wardhani, Firdha Aprillia (Pharmaciana, 2025)
Indonesia has a long history of using medicinal plants, but much of this knowledge, especially among groups like the Osing people in East Java, is not well-documented. This study looks at the plants used by the Osing community to treat diarrhea. This research was conducted through interviews with residents of Banjar and Licin Villages in Banyuwangi Regency. The significance and perceived efficacy of each medicinal plant were evaluated using the ethnobotanical indices Use Value (UV) and Fidelity Level (FL). They also did tests to find the active chemicals in the plants. The most common plants for treating diarrhea were Psidium guajava (UV = 2.44) and Piper betle (UV = 1.11). Psidium guajava had the highest FL value (64.7%). Tests have shown that these plants contain essential chemicals. Further analysis confirmed the presence of quercetin and kaempferol, which are known to help alleviate stomach problems. To support these findings, computer-based tests were done, including Lipinski rule prediction, ADMET profiling, and molecular docking. The results showed quercetin binds well (ΔG = -9.72) and has a good RMSD value (1.83 Å). This suggests quercetin could be a good starting point for making antidiarrheal drugs. Overall, the study underscores the significance of traditional knowledge and recommends further research on plant-based treatments for stomach issues.